Assessment of socio demographic factors on termination of pregnancy in Ghana - Mavis Akosuah Serwah Armah‐Mensah; Isaac Armah‐Mensah (Wiley, 2024)
Abstract Aim Assessing the socio‐demographic factors on termination of pregnancy in Ghana. Design Cross‐sectional study, using data source from the Demographic Health Survey (DHS). Methods Data pooled from the most recent DHS conducted in Ghana, with variables of interest with rural and urban population coverage. A systematic search of the literature was performed using PubMed, Google Scholar and Elsevier PubMed for the secondary data. Descriptive and logistic regression analysis was performed using Python Pandas' software to estimate the independent effects of the socio‐demographic factors on termination of pregnancy in Ghana. Results Reported using odds and adjusted OR AOR at 95% confidence level and statistical significance at a p‐value of (p > 0.05). Age, place of residence, occupation, currently pregnant, woman's individual sample weight, completeness of current pregnancy, living children + current pregnancy, ethnicity and number of living children significantly predicted the outcome variable. Patient or Public Contribution Nurses have an important role to play in providing support, education and counselling to people, and must be equipped with the knowledge and skills (including non‐judgmental and compassionate care) necessary to provide care that is sensitive to the diverse needs of people from different socio‐demographic backgrounds.